RANCANG BANGUN MESIN BOR TANAH UNTUK MEMBUAT LUBANG RESAPAN AIR (BIOPORI) - Sailon, Sailon; Zamheri, Ahmad; Wilza, Romi; Zainuddin, Zainuddin (Politeknik Negeri Sriwijaya, Indonesia, 2017)
The designed biopore drill machine uses manual manual hoist / manual crank system that serves to raise and lower the drill bit. Engines that are connected to the drill bit vertically in addition to functioning to rotate the drill bit also serve as a weight so that the drill bit can enter the ground. In addition, the biopori drill machine is made of a rectangle with the aim that the machine at the time of operation becomes steady (not shifted) and the legs are wheeled in order tobe easy to move around. Biopori drill machine is a modification of existing tools, both variations of the form and additional accessories, with the aim to facilitate the operation, transfer and optimize the work with a relatively low cost and physical fitness of the operator is maintained and safety can be more.secure. This research focuses on designing the shape and size of the machine so that it is easy to operate and transfer, calculating the strength of eachÂ component in accordance with the scientific method and testing the engine performance. The purpose of this study is expected to contribute to technology in the form of: to produce a prototype in order to enrich khasana appropriate equipment that can be utilized to help the manufacture of biopore holes, improve the quality and quantity of infrastructure equipm entresear chinstitute sustainable. In designing the build of this biopori drill first collect planning data.Â A part from field data the data is taken from the literature.